Single women and motherhood: right now or maybe later? - Désirée García; Rita Vassena; Amelia Rodríguez (Taylor & Francis Group, 2020)
Purpose: The decision to have a child might be postponed by the lack of partner, and elective egg freezing (EEF) can afford single women more time to find a suitable companion to reach the desired family structure. Alternatively, some women decide to have a child on their own thorough in vitro fertilization (IVF) or intrauterine insemination (IUI) with donor sperm. This study investigates the motivations and personal characteristics of single women undergoing IVF/IUI or EEF. Materials and methods: This is a cross-sectional study including 281 heterosexual single women who underwent either IVF/IUI with donor sperm for solo motherhood (208) or EEF (73) in 2015 at a large fertility center. An anonymous electronic survey was sent after starting the treatment. Results: The most common reason for not having fulfilled the motherhood desire was lack of partner (72.4% IVF/IUI and 65.9% EEF). We found that women undergoing IVF/IUI report a longer motherhood desire, >10 years (71.3% vs. 54.3%), live closer to their families (75.5% vs. 56.5%), and perceive a stronger family support than women undergoing EEF (85.4% vs. 68.8%). Finally, 100% of EEF obviously knew about the possibility of IVF/IUI with donor sperm, while 59.9% of IVF/IUI knew about EEF. Conclusion: Our results underscore the relevance of family ties in the decision to undergo IVF/IUI as single women. Moreover, these women might not be fully informed about social freezing as an option to postpone motherhood. Health professionals should be aware of these differences when counseling single women on fertility choices.